2015
DOI: 10.5861/ijrsp.2015.774
|View full text |Cite
|
Sign up to set email alerts
|

The role of personality and intercultural effectiveness towards study abroad academic and social activities

Abstract: With the current trend of higher education study abroad exchanges, opportunities for travelling and studying in another country are at an all-time high. These exchanges are noted for providing both academic and sociocultural benefits. However, these heightened opportunities have also started to cause parents and academics to wonder about the quality of such experiences. Literature suggests that the students' personality and their intercultural competencies play an important role in the success of their study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…This also holds true for Taiwan, wherein the decreasing number of incoming local university enrollees has opened up the opportunity to recruit more foreign students (Wang & Ching, 2015). Therefore, in order to promote Taiwan as a quality venue for study abroad it is quite important to know what study abroad students are currently doing and/or how they are preparing for/handling their academic studies.…”
Section: Introductionmentioning
confidence: 99%
“…This also holds true for Taiwan, wherein the decreasing number of incoming local university enrollees has opened up the opportunity to recruit more foreign students (Wang & Ching, 2015). Therefore, in order to promote Taiwan as a quality venue for study abroad it is quite important to know what study abroad students are currently doing and/or how they are preparing for/handling their academic studies.…”
Section: Introductionmentioning
confidence: 99%
“…Results from a study by Wen-Lin and Gregory (2015) showed that individual scores of the Intercultural Effectiveness Scale (IES) [ 54 ], which measures overall cultural competence and intercultural attitudes, were positively correlated with the Big-Five Personality Inventory factors [ 55 ]. More specifically, they showed that six IES factors, namely, behavioral flexibility, interaction relaxation, interactant respect, message skills, identity maintenance, and interaction management, were positively correlated with four personality factors (extraversion, agreeableness, conscientiousness, openness).…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is supported by the conclusions by Kehl and Morris based on the literary review: female students are more susceptible to the impact of studying abroad, as their thinking becomes more global [45]. The opposite conclusions were reached by Wang and Ching, who showed that some indicators of intercultural effectiveness ("relaxation in interaction" and "management of interaction") are higher among young men [49]. Using the Russian adaptation of the DMIS, Logashchenko revealed that male and female samples differ on the Absolutization scale: women are more confident than men in their ability to control the influence of cultural differences on the communication process [23].…”
Section: Introductionmentioning
confidence: 88%